Modeling Risk Factors for Total Paralysis of Stroke Patients in RSUD Dr. R. Sosodoro Djatikoesoemo Bojonegoro Using Binary Logistic Regression - Puji Hidayatus Sholikhah; Sri Pingit Wulandari (Institut Teknologi Sepuluh Nopember, 2020)
One of the causes of death in Bojonegoro Regency is stroke. Stroke is a nervous system function disorder that occurs suddenly and is caused by circulatory disorders of the brain. From 2015 to March 2018, stroke has always been ranked first as the type of disease that most patients suffer in RSUD Dr. R. Sosodoro Djatikoesoemo Bojonegoro. Stroke can cause sufferers to experience limited ability to carry out daily activities (eating, dressing, defecating, bathing, and moving) because there are limbs that are paralyzed so it is difficult to move. Therefore, this study aims to describe the characteristics of stroke patients and to analyze the risk factors that cause stroke patients get totally paralyzed using binary logistic regression. The data used in the form of secondary data obtained from the results of medical records of stroke patients who were hospitalized at RSUD Dr. R. Sosodoro Djatikoesoemo Bojonegoro from January to March 2018. Based on the results of the analysis showed that the majority of stroke patients are over 55 years old and males also the risk factors that cause stroke patients geet totally paralyzed are the type of stroke and previous history of stroke.